Graceful labeling on torch graph - Jona Martinus Manulang; Kiki A. Sugeng (Indonesian Combinatorial Society (InaCombS), 2018)
Let G be a graph with vertex set V = V(G) and edge set E = E(G). An injective function f : V → 0, 1, 2, ..., ∣E∣ is called graceful labeling if f induces a function f * (uv) = ∣f(u) − f(v)∣ which is a bijection from E(G) to the set 1, 2, 3, ..., ∣E∣. A graph which admits a graceful labeling is called a graceful graph. In this paper, we show that torch graph On is a graceful graph.